Combating the motivational constraint barrier in legal aid participation by lawyers in the judiciary - Garcia, Karina Mae P. (2023)
The recent released Code of Professional Responsibility and Accountability introduces a provision generally prohibiting government lawyers from engaging in the private practice of law. This Article examines such provision as applied to lawyers in the judiciary, along with the other related laws. rules, and jurisprudence on private practice, and demonstrates how it engenders a "motivational constraint" that discourages such lawyers from participating in legal aid. To overcome such constraint, the Article considers the American approach: one that provides for a straightforward rule expressly recognizing legal aid as an exception to the general prohibition and setting out all the conditions for such activity.
Keywords: Practice of law; Government attorneys; Legal professions; Code of Professional Responsibility and Accountability